Toronto School of Communication Theory - Vekua, Konstantin (New Explorations, 2025)
Toronto School of Communication Theory is not only a success story but also avision and practice of creating and building the country's intellectual future. For decades,scholars at Canada's leading university have contributed to their homeland's originaldevelopment, choosing the paradigm of orientation between economy and history, differentfrom the development paths of the United States and Europe. Finding one's niche in the worldof ideas and innovations is a result of the need to overcome the challenges faced by society.For this purpose, collective intellect is one of the efficient tools that the illustriousrepresentatives of the School of Communication Theory in Toronto offer. Multidisciplinarity, asa working method, has profoundly influenced the evolution of the concept of communication inthe university environment, which contributed to the growth of contemporary political thought(and not only) in Canada and abroad.